Innovation and efficiency in financial institutions - Sena, Vania; Kenjegaliev, Amangeldi; Kenjegalieva, Aliya (Frontiers in Research Metrics and Analytics, 2022)
In this paper we investigate the quality of innovation and efficiency of financial institutions. We transform a production frontier curve into a single frontier point to detect the quality. Our modified distance function employs an innovation rank and an overall rank. Innovation activity is ranked according to size of such an activity while labour and assets are combined into the overall rank. As a robustness check, we examine the relationship between non-performing loans and the overall rank. Our data on US and EU banks spans from 2010 to 2019 and consists of 42,405 bank-year observations. We find that the inefficient unit does not have the worst innovation or overall ranks. Rather a combination of them scores the unit as an inefficient unit. The key findings indicate four types of innovating banks based on the quality of innovation. First, the banks where the innovation rank is positively correlated with the combined rank. The second type of banks exhibit negative correlation between two ranks: their overall rank decreases as banks improve the innovation rank. Despite having high overall rank, the innovation score for the third type of banks is only slightly better than the average rank. Banks in the final group are the least efficient/preferred with the worst ranks of all four groups.